2012
DOI: 10.1016/j.febslet.2012.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of solvent tolerance in Pseudomonas putida DOT‐T1E based on its genome sequence and a collection of mutants

Abstract: Pseudomonas putida strains are prevalent in a variety of pristine and polluted environments. The genome of the solvent‐tolerant P. putida strain DOT‐T1E which thrives in the presence of high concentrations of monoaromatic hydrocarbons, contains a circular 6.3 Mbp chromosome and a 133 kbp plasmid. Omics information has been used to identify the genes and proteins involved in solvent tolerance in this bacterium. This strain uses a multifactorial response that involves fine‐tuning of lipid fluidity, activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 73 publications
(115 reference statements)
0
31
0
Order By: Relevance
“…As the number of characterized TCSs grows, the inventory of variations on the basic scheme also grows (34,35). In this study, we have shown that the GrtS/GltR regulators form a previously unidentified TCS.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of characterized TCSs grows, the inventory of variations on the basic scheme also grows (34,35). In this study, we have shown that the GrtS/GltR regulators form a previously unidentified TCS.…”
Section: Discussionmentioning
confidence: 99%
“…Any of these are candidates for manipulation to cause the efflux of biotechnological products. Known ones include those for dipeptides [340], antibiotics [132,133,135,136], and solvents [133,341,342]. Broadly similar statements are true in S. cerevisiae, where a variety of efflux pumps help remove intracellular toxicants of all kinds [343][344][345][346][347][348].…”
Section: Directed Evolution: Changing the Sequence Of The Target Tranmentioning
confidence: 99%
“…This topic has been explored from the viewpoint of bioremediation of hydrocarbon spills and contamination, biocatalysis using whole microbes in two-phase solvent systems, and the production of solvent-like compounds. Several recent and thoughtful reviews [3,4,9,[13][14][15][16] and comprehensive systems biology studies [17][18][19][20][21][22][23][24][25][26][27] focus on evaluating solvent tolerance across numerous bacterial hosts (also see Box 1). Although a given solvent will elicit specific stress responses, some generalizable trends are now established.…”
Section: Mechanisms Of Solvent Toxicity In Bacteriamentioning
confidence: 99%
“…Solvent-tolerant microbes and choice of microbial host strains Pseudomonads are some of most solvent-tolerant microbes. With extensive and redundant capacities for short-term (cis-to-trans [28]) and long-term (increase in saturation [32]) phospholipid fatty acid (PLFA) modifications and potent efflux systems (TtgABC, TtgDEF, and TtgGHI in Pseudomonas putida DOT-T1E [26,67] and SrpABC in P. putida S12 [15]), these microbes have superior tolerance to BTEX (benzene, toluene, ethylbenzene, xylene) chemicals as well as other hydrocarbons (e.g., n-hexane, cyclohexane). In general their native resilience toward compounds with log P < 4 (Box 1) is higher than industrial hosts such as Escherichia coli.…”
Section: Reviewmentioning
confidence: 99%